Model Latihan Menyerang Sepakbola Usia 16 Tahun - Valentino Hary; Bahtiar Firdiansyah (STKIP Muhammadiyah Kuningan, 2020)
The aim of this research is to produce a training model for attacking football and also to refute its effectiveness for children aged 16 years. As for the steps in developing the research, the Borg and Gall steps involved 15 subjects for the small test and 60 for the large test. Qualitative data were obtained from observations, documentation and interviews; meanwhile, for the quantitative data using the effectiveness test. The trial of this study used pre and post tests with 10 opposing criteria. In mathematical calculations the significance of the difference t-count = -28.971, db = 43 and p-value = 0.00 <0.05, which means it contains significance before and after giving treatment. It can be concluded that the model is applied effectively to improve the ability for attacking amongst school students aged 16 years. Thus, representing the differences in motor skills highlights the principle of specificity for attacking training at the age of 16 must be considered that the load of portions in the exercise program can be maximized.